Investigation of the role and quantitative impact of breast cancer resistance protein on drug distribution into brain and CSF in rats. (February 2022) - Katagiri, Yuki; Kawaguchi, Hiroko; Umemura, Koji; Tadano, Jun; Miyawaki, Izuru; Takano, Mikihisa
Abstract: Breast cancer resistance protein (BCRP) expressed in the blood-brain barrier plays a major role in limiting drug distribution into the central nervous system (CNS). However, functional involvement of BCRP in drug distribution into the brain and cerebrospinal fluid (CSF) remains unclear. The aim of present study was to reveal the role and quantitative impact of BCRP on CNS distribution. The brain-to-plasma unbound concentration ratio (Kp, uu, brain ) and CSF-to-plasma unbound concentration ratio (Kp, uu, CSF ) values of BCRP-specific substrates were determined in rats. The Kp, uu, brain values decreased, as the in vitro BCRP corrected flux ratio (CFR) increased. The Kp, uu, CSF values of BCRP-specific substrates were greater than the Kp, uu, brain values. Increase in the Kp, uu, brain values induced by co-administration of BCRP inhibitor correlated with the in vitro BCRP CFR and were greater than the increase in Kp, uu, CSF values induced by BCRP inhibitor except nebicapone. The contribution of BCRP to the brain and CSF distribution of the dual P-glycoprotein/BCRP substrates, imatinib and prazosin, was similar to that of BCRP-specific substrates. Thus, we revealed that the impact of in vivo BCRP on CNS distribution is correlated with in vitro BCRP CFR, and that BCRP limits drug distribution into the brain more strongly than into the CSF. Graphical abstract: Image 1